Linger - Stiefvater, Maggie, 1981- (Scholastic, 2010)
Grace and Sam must fight to be together. For Grace, this means defying her parents and keeping dangerous secrets. For Sam, it means grappling with his werewolf past ...and figuring out a way to survive the future. But just when they manage to find happiness, Grace finds herself changing in ways she could never have expected..